Biomorphological determination of Gymnospermium odessanum (DC.) Takch. as an ephemeric geophyte (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Early ontomorphogenetic specialization of Gymnospermium оdessanum (DC.) Takch. as ephemeroid geophyte has been recorded. Its extrapolation on the phylogenetic level as a ascertaining of the relative evolutional statics of the species was proposed.
Keywords: Gymnospermium оdessanum, ontomorphogenesis, specialisation, ephemeroid geophyte.